Porous microspheres of manganese-cerium mixed oxides by a polyvinylpyrrolidone assisted solvothermal method. (April 2017) - Schmit, F.; Bois, L.; Chiriac, R.; Toche, F.; Chassagneux, F.; Descorme, C.; Besson, M.; Khrouz, L.
Abstract: Mixed cerium manganese oxides were synthesized using a polyvinylpyrrolidone (PVP) assisted solvothermal method. Materials obtained after calcination at 400 °C were characterized by X-ray diffraction, scanning and transmission electron microscopies, electron paramagnetic resonance (EPR), Raman spectroscopy, thermal analysis and nitrogen adsorption/desorption isotherms. The influence of the synthesis parameters on the oxide structure, such as the Mn:Ce ratio or the amount of PVP, was discussed. Micrometric spheres of mixed Mn-Ce oxides, resulting from the aggregation of 100 nm porous snowflakes, were successfully synthesized. These snowflakes were formed from the aggregation of smaller oriented crystallites (size 4 nm). The hydrothermal stability of these materials was also investigated. Graphical abstract: Highlights: Mixed manganese cerium oxides were synthesized, with polyvinylpyrrolidone as capping ligand. Micrometric spheres were formed from aggregation of 100 nm diameter porous snowflakes. Snowflakes were formed from aggregation of 4 nm Mn-Ce oxides oriented crystallites. For Mn:Ce ratio increasing, the ceria crystallites orientation decreased.